Transplantation of preserved human amniotic membrane for perforated bacterial corneal ulcer and persistent epithelial defects, Cases Study. - Suhardjo, Suhardjo (Universitas Gadjah Mada, 2002)
Background: Human amniotic membrane has anti-adhesive properties and is felt to promote epithelization and decrease inflammation. Fresh human amniotic membrane transplantation has been shown to be effective in the reconstruction of the corneal surface in the setting of persistent epithelial defects, sterile corneal ulcerations, and partial limbal stem cell deficiency.Objectives: The purpose of this study is to report two cases of perforated bacterial corneal ulcer and one case persistent epithelial defect treated by preserved human amniotic membrane transplantation and to determine whether preserved human amniotic membrane transplantation can be used as an alternative method for treating perforated bacterial corneal ulcer.Methods: Observed human amniotic membrane transplantation was performed on 2 eyes of 2 patients with perforated bacterial corneal ulcer and one case with persistent epithelial defect of different causes. The amniotic membrane was placed on the surface of the cornea in overlay and secured by interrupted 10.0 nylon sutures to the surrounding conjunctiva.Results: There was significant improvement of the visual acuity in case 3 with persistent epithelial defect. Despite absence of improvement of the visual acuity in cases 1 and 2, the epithelization occurred in all patients and the perforated ulcers healed. As a wound dressing, human amniotic membrane has a number of benefits: in both patients the decreased inflammatory reaction, diminishes pain and increases the ocular mobility, and may help in prediction of readiness for grafting.Conclusion: Preserved human amniotic membrane transplantation may be considered as an alternative method for treating perforated bacterial corneal ulcer which is refractory to conventional treatment.Key words: amniotic membrane transplantation - decrease inflammation - perforated corneal ulcer -persistent epithelial defect - readiness for grafting.